An Integration of Buddhist Moral Codes Promoting Behavioral and Cognitive Transformations amongst Industrial Entrepreneurs - Buracom, Khemanij (Journal of International Buddhist Studies, 2017)
The purposes of this study are to investigate the factors and related elements that promote behavioral and cognitive transformations amongst industrial entrepreneurs on a personal level; to ascertain the Buddhist moral codes that promote such transformations; to study the integration of Buddhist moral codes that promote changes on a corporate level; and to develop a model integrating Buddhist moral codes for overall change. Thirty in-depth semi-structured interviews amongst industrial entrepreneurs were undertaken in order to explore their behaviors, thoughts, and experiences related to Buddhism and the integration of Buddhist moral codes promoting changes on a corporate level. The combination of analytical qualitative and quantitative techniques was used to eliminate the disadvantages of each technique and to increase the reliability and validity of the research findings. Regression analysis was used to statistically predict the four studied factors influencing changes on personal and corporate levels. Descriptive statistics were used to quantitatively describe the basic features of data and to support the qualitative results in order to make the research findings more elaborate and precise. Regarding personal transformations, spiritual experiences through samadhi were the most influential factors promoting such changes, followed by dhamma experiences through reading books and listening to dhamma speeches, personal backgrounds, and business conditions respectively. The discovered top-five personal changes were to: (1) texhibit greater loving-kindness; (2) be more generous; (3) attend dhamma retreats more; (4) be willing to share Buddhist moral codes with employees; and (5) become extensive dhamma readers and gain better understanding of dhamma. Amongst the eleven favorite Buddhist moral codes influencing personal transformations, the top-five included: (1) the Four Sublime States; (2) Gratitude and Gratefulness; (3) the Three Basic Facts of Existence; (4) the Law of Karma; and (5) the Four Noble Truths and the Four Successful Paths. In terms of corporate transformations, spiritual experiences still remained the most influential factor, followed by business conditions. Making employees become good, kind, and happy persons was the utmost inspiration regarding this matter. Various types and methods of activities were designed to serve as tools for the integration of Buddhist moral codes. The outcomes mainly were divided into two aspects, employees and overall business. Due to the positive effects on employees, they (1) became happier; (2) had better relationships with executives; (3) became more helpful and generous with each other; (4) showed more willingness to work without conditions; and (5) showed better manners towards others as well as showed more willingness to help executives solve problems. The contributions to overall business were to: (1) gain more trust between executives and employees; (2) have less conflict amongst employees; (3) increase work efficiency; (4) solve problems more carefully; (5) and have higher business turnover. A model integrating Buddhist moral codes for overall change (at both personal and corporate levels) was fully developed by providing details and a rich picture in order to enhance the ease of implementation. The model began with classifying industrial entrepreneurs into four groups. The first group was set as successful examples. The second and third groups were considered to be individuals that demonstrated a potential for development, whereas the fourth group was not taken into account due to due to the individuals’ demonstrated lack of potentiality for development. Network building allowed the target groups to get together and share experiences. Regarding the second and third groups, their interests needed to be stimulated concerning the integration of Buddhist moral codes for overall change. Three channels of stimulation were to: (1) learn from the experiences of the first group; (2) gain confidence through research findings; and (3) cultivate themselves through accepting problems, knowing the causes of problems, picturing a company where problems were completely solved, and finding solutions to problems. After personal transformations, they would seriously put the integration of Buddhist moral codes into action. Four suggested guidelines were to: (1) directly focus on Buddhist ways; (2) apply activities associated with focused Buddhist moral codes to fit the lifestyles of employees; (3) improve the quality of employees’ lives; and (4) create a workplace environment to support the changes. The contributions of this study to the body of knowledge are comprised not only of the combination of qualitative and quantitative analyses but also the factors promoting overall change, Buddhist moral codes, and various activities as tools for integrating Buddhist moral codes. Moreover, the development of a model as a guideline for further integrating Buddhist moral codes to promote overall change consequently became a strong contribution of the study.